ETIKA PROFESI DALAM PENERAPAN TEKNOLOGI BIM PADA PROYEK KONSTRUKSI: PERSPEKTIF INSINYUR SIPIL - Manurung, Edison Hatoguan; Hutagaol, Kerlima; Putrafakhmi, Dizzy (SINERGI : Jurnal Riset Ilmiah, 2025)
The use of Building Information Modeling (BIM) technology in construction projects has had a significant impact on the work processes of civil engineers. However, this advancement also raises new ethical challenges. This paper examines the application of professional ethics in the use of BIM from the perspective of civil engineers. Through a qualitative approach and literature review, it was found that while BIM improves efficiency and collaboration, integrity and professional responsibility are still required to prevent data misuse or violations of ethical principles. Ethics are key to maintaining project quality and accountability in the digital age.